Innovating for elderly people: the development of geront'innovations in the French silver economy. Issue 4 (3rd April 2019) - Laperche, Blandine; Boutillier, Sophie; Djellal, Faridah; Ingham, Marc; Liu, Zeting; Picard, Fabienne; Reboud, Sophie; Tanguy, Corinne; Uzunidis, Dimitri
ABSTRACT: The objective of this paper is to study the supply side of the silver market, which is usually neglected by research on this topic. Adopting a systemic approach to innovation, our main goals are to identify the nature of the innovations developed, the way innovations are created, and the issues related to their emergence and diffusion. Our research is based on an empirical study of the French silver economy, which consists in an enquiry carried out in Silver Valley. The results of our study lead us to suggest a new term 'geront'innovation' to qualify the various forms of innovations developed to cater for the needs of elderly people. We also put forward the importance of networking and open innovation strategies. Finally, the identified barriers to emergence and diffusion as perceived by the supply side of the market lead us to suggest recommendations to support the diffusion of geront'innovations.